Nutrient content affects the turnover of fungal biomass in forest topsoil and the composition of associated microbial communities - Brabcová, Vendula; Štursová, Martina; Baldrian, Petr (Soil biology & biochemistry, 2018)
Due to the standing biomass and turnover of fungal biomass in forest topsoils, decomposition of fungal biomass represents an important process. Within plant litter, dead fungal biomass represents a unique substrate that is typically nitrogen (N)-rich and is assumed to be subject to rapid decomposition. However, our current knowledge of mycelial decomposition has been largely derived from short-term studies, often limited to a single mycelia type, and the guilds of microbial mycelium decomposers have not yet been described. Furthermore, nutrient content may vary largely in fungal mycelia, and the consequences of this variation are unknown. Here, we followed the decomposition of dead biomass of 12 ectomycorrhizal (ECM) and saprotrophic fungi of a temperate forest using mycobags incubated in litter for 3 and 9 weeks. Loss of substrate dry mass, microbial biomass content and community composition as well as the activity of extracellular enzymes reflecting microbial activity on this substrate were followed. Decomposition rates of fungal biomass were typically high (0.13–0.30 week−1), yet variable. The decomposition includes a rapid initial phase followed by a slower turnover of remaining biomass. The initial nitrogen content that ranged between 1.5% and 10% appeared to be the most important factor that affected colonization of dead mycelia and their decomposition. The relatively high content of N makes fungal mycelia an attractive resource in the N-poor habitat of plant litter. Decomposition of mycelia was performed by a guild of specialist decomposers that showed rather low abundance in surrounding litter and changed during decomposition. Bacteria were much more abundant on dead fungal biomass than in the surrounding litter and appeared to play an important role in decomposition. Fungi associated with dead mycelia were mainly represented by yeasts and moulds. Although the importance of fungal mycelia for the nutrient cycling in forests is not yet clear, the fact that they are turned over rapidly suggests that they may represent an important and dynamic pool of carbon and nitrogen. [Display omitted] •Turnover of dead fungal biomass in forest topsoil is affected by nutrient content.•Mycelia represent unique habitats with high bacterial biomass and rapid turnover.•Bacteria, yeasts and moulds are major associates of decomposing fungal biomass.•Bacterial and fungal decomposers change during succession on dead fungal biomass.